2018
DOI: 10.1007/s12553-018-0267-x
|View full text |Cite
|
Sign up to set email alerts
|

Providers’ perspectives on adherence to hormonal therapy in breast cancer survivors. Is there a role for the digital health feedback system?

Abstract: Objective: Despite the benefits of hormonal therapy (HT) adherence remains suboptimal in ER positive breast cancer patients. Medication adherence is challenging to assess and tends to be overestimated. The Digital Health Feedback System (DHFS) consists of an ingestible sensor attached to a pill that sends intake date and time to a smart phone or computer. Patients can share this information with health care providers and other persons. The DHFS can also send reminders. This mixed methods study examined provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In addition, the discrepancy between intention and behavior may be relevant. In this study, AI continuation intention was measured instead of adherence (i.e., a behavioral variable), considering the lack of reliability and evidence regarding self-reported measures of medication adherence [29]. Although intention to take medication is a predictor of medication adherence [6], actual behavior can differ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the discrepancy between intention and behavior may be relevant. In this study, AI continuation intention was measured instead of adherence (i.e., a behavioral variable), considering the lack of reliability and evidence regarding self-reported measures of medication adherence [29]. Although intention to take medication is a predictor of medication adherence [6], actual behavior can differ.…”
Section: Discussionmentioning
confidence: 99%
“…Identified as eligible: (Accordino & Hershman, 2013 ; Banning, 2012 ; Cahir, Guinan, et al, 2015 ; Chlebowski et al, 2014 ; Gotay & Dunn, 2011 ; Lambert, Balneaves, Howard, & Gotay, 2018 ; Mausbach et al, 2015 ; McCowan & Thompson, 2012 ; Miaskowski et al, 2008 ; Milata et al, 2018 ; Moon, Moss‐Morris, Hunter, Carlisle, et al, 2017; Murphy et al, 2012 ; Paranjpe et al, 2019 ; Puts et al, 2014 ; Sawesi et al, 2014 ; Van Liew et al, 2014 ; Wassermann & Rosenberg, 2017 )
APPENDIX B2 Flow chart qualitative articles. Identified as eligible: (Bluethmann et al, 2017 ; Brett et al, 2018 ; Cahir, Dombrowski, et al, 2015 ; Farias, 2016 ; Farias et al, 2017 ; Hackett et al, 2018 ; Harrow et al, 2014 ; Humphries et al, 2018 ; Hurtado‐de‐Mendoza, Cabling, et al, 2019 ; Iacorossi et al, 2018 ; Lambert, Balneaves, Howard, Chia, et al, 2018; Moon, Moss‐Morris, Hunter, & Hughes, 2017 ; Pellegrini et al, 2010 ; Pieters et al, 2019 ; Samuel et al, 2017 ; Toledo et al, 2019 ; van Londen et al, 2014 ; Wheeler et al, 2015 ; Wouters et al, 2013 ; Yamamoto et al, 2015 )
APPENDIX B3 Flow chart quantitative articles. Identified as eligible: (Brett et al, 2018b ; Cabling et al, 2018 ; Hagen et al,
…”
Section: Appendix B1mentioning
confidence: 99%
“… Flow chart qualitative articles. Identified as eligible: (Bluethmann et al, 2017 ; Brett et al, 2018 ; Cahir, Dombrowski, et al, 2015 ; Farias, 2016 ; Farias et al, 2017 ; Hackett et al, 2018 ; Harrow et al, 2014 ; Humphries et al, 2018 ; Hurtado‐de‐Mendoza, Cabling, et al, 2019 ; Iacorossi et al, 2018 ; Lambert, Balneaves, Howard, Chia, et al, 2018; Moon, Moss‐Morris, Hunter, & Hughes, 2017 ; Pellegrini et al, 2010 ; Pieters et al, 2019 ; Samuel et al, 2017 ; Toledo et al, 2019 ; van Londen et al, 2014 ; Wheeler et al, 2015 ; Wouters et al, 2013 ; Yamamoto et al, 2015 ) …”
Section: Appendix B1mentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of publications on oral anticancer medications from 2003 to 2015 showed that medication adherence rates varied widely from 46% to 100% [ 7 ]. In interviews with patients with breast cancer, de Mendoza et al [ 8 ] found that 78.9% of the patients failed to report medication discontinuation immediately and 57.9% overreported medication adherence.…”
Section: Introductionmentioning
confidence: 99%